Response to Comment on ``Radiative Absorption Enhancements Due to the Mixing State of Atmospheric Black Carbon'' - Cappa, Christopher D.; Onasch, Timothy B.; Massoli, Paola; Worsnop, Douglas R.; Bates, Timothy S.; Cross, Eben S.; Davidovits, Paul; Hakala, Jani; Hayden, Katherine L.; Jobson, B. Tom; Kolesar, Katheryn R.; Lack, Daniel A.; et al. (SCIENCE, 2013)
Jacobson argues that our statement that ``many climate models may overestimate warming by BC'' has not been demonstrated. Jacobson challenges our results on the basis that we have misinterpreted some model results, omitted optical focusing under high relative humidity conditions and by involatile components, and because our measurements consist of only two locations over short atmospheric time periods. We address each of these arguments, acknowledging important issues and clarifying some misconceptions, and stand by our observations. We acknowledge that Jacobson identified one detail in our experimental technique that places an additional constraint on the interpretation of our observations and reduces somewhat the potential consequences of the stated implications.